2018
DOI: 10.1016/j.resuscitation.2018.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Electro-clinical characteristics and prognostic significance of post anoxic myoclonus

Abstract: Early onset PAM is not always associated with lack of recovery of consciousness. EEG can help discriminate between patients who may or may not regain consciousness by the time of hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…However, such specific changes were not seen in the available CT scans during the acute stage. Recent studies analyzing the electro‐clinical significance of aPHM after SCA have reported the presence of midline/vertex spikes over a continuous background as a favorable prognostic marker 10,12 . It is unclear if the vertex and frontocentral location of IEDs in our cohort is an electrographic vestige from the acute stage.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, such specific changes were not seen in the available CT scans during the acute stage. Recent studies analyzing the electro‐clinical significance of aPHM after SCA have reported the presence of midline/vertex spikes over a continuous background as a favorable prognostic marker 10,12 . It is unclear if the vertex and frontocentral location of IEDs in our cohort is an electrographic vestige from the acute stage.…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies analyzing the electroclinical significance of aPHM after SCA have reported the presence of midline/vertex spikes over a continuous background as a favorable prognostic marker. 10,12 It is unclear if the vertex and frontocentral location of IEDs in our cohort is an electrographic vestige from the acute stage. On the other hand, it could represent a signature, long-term epileptogenic marker in the SCA survivors.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, it is recommended to evaluate them in combination with other prognostic tests. 102,119,127,129,131,[139][140][141][142][143] EEG recordings may also be considered in case of status myoclonus to find related epileptic activity.…”
Section: Clinical Examinationmentioning
confidence: 99%